2022
DOI: 10.1038/s41598-022-09193-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in esophageal cancer overall and by histological subtype

Abstract: Esophageal cancer is the seventh most common type of cancer in the world, the sixth leading cause of cancer-related death and its incidence is expected to rise 140% in the world in a period of 10 years until 2025. The overall incidence is higher in males, while data about prognosis and survival are not well established yet. The goal of this study was to carry out a comprehensive analysis of differences between sexes and other covariates in patients diagnosed with primary esophageal cancer. Data from 2005 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
(35 reference statements)
1
23
0
Order By: Relevance
“…5 However, different survival analysis models have not shown differences between men and women. 4 Recent studies suggested that almost 90% of cases occur in individuals aged 55 years or older. 1,2 The two most common histological cancer types include esophageal adenocarcinoma (EAC) and esophageal squamous cell carcinoma (ESCC), 6 which usually occur in either the proximal (ESCC) or distal (EAC) esophagus, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…5 However, different survival analysis models have not shown differences between men and women. 4 Recent studies suggested that almost 90% of cases occur in individuals aged 55 years or older. 1,2 The two most common histological cancer types include esophageal adenocarcinoma (EAC) and esophageal squamous cell carcinoma (ESCC), 6 which usually occur in either the proximal (ESCC) or distal (EAC) esophagus, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It has the potential to metastasize at early stages and is characterized by disproportionally high mortality rates and a poor prognosis 2,3 . EC occurs more often in males than in females and becomes more common with older age 2,4 . Furthermore, among American inhabitants, men have around four‐fold higher death rates 5 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations